The Knowledge and Use of Speech Therapy Mobile Applications: Speech-Language Pathologists’ Perspectives in Malaysia - Kamaruddin, Afiqah Iylia; Masrom, Maslin; A Aziz, Mohd Azmarul; Garraffa, Maria; Mohd Noor, Norliza (International Journal of Integrated Engineering, 2023)
Technology incorporation in speech therapy has been growing over the years. Mobile applications are among the adoptions that facilitate delivering speech therapy services. The situation in Malaysia is discouraging because there are not enough speech-language pathologists (SLPs) to serve the growing number of populations. Despite the abundance of available speech therapy mobile applications in the market, there is a lack of information focusing on the SLP’s knowledge and usage perspectives, especially in Malaysia. The objectives of this study are to describe the knowledge and usage perspectives of speech therapy mobile applications among SLPs in Malaysia and to analyze the instructional features and functional features relationships within the perspectives of SLPs. Surveys are established in three parts, with demographic questions in Part A, Likert scale responses for statements in Part B, and open-ended questions in Part C. This study is co-designed to relate to the results from an initial study that adopted PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and features analysis. The data from the initial study includes a review of 161 apps out of 1797 that have been identified. Five instructional features and nine functional features are presented. There are 35 SLPs participating in the survey. Their responses demonstrate evidence of SLPs’ knowledge and usage of speech therapy mobile applications. We will propose a conceptual framework for the features of speech therapy mobile applications, using people with aphasia as a point of reference for users with speech and language disorders.